Biologic Abatement and Capturing Kids’ Outcomes and Flare Frequency in Juvenile Spondyloarthritis (BACK-OFF JSpA): study protocol for a randomized pragmatic trial - Pamela F. Weiss; Cora E. Sears; Timothy G. Brandon; Christopher B. Forrest; Emily Neu; Melanie Kohlheim; Jenny Leal; Rui Xiao; Daniel Lovell (Trials, 2023)
Abstract Background The effectiveness of biologic therapies, primarily tumor necrosis factor inhibitors (TNFi), for children with spondyloarthritis (SpA) has made inactive disease a realistic patient outcome. However, biologic therapies are costly, primarily delivered by subcutaneous or intravenous route, and have non-trivial side effects. Many patients and families want to know if biologic medications can be discontinued after inactive disease is achieved. It remains unclear whether medication dose should remain unchanged, tapered (increase the time between doses), or discontinued once when inactive disease is attained. Methods The Biologic Abatement and Capturing Kids’ Outcomes and Flare Frequency in Juvenile SpA (BACK-OFF JSpA) trial is a multicenter pragmatic trial that will randomize 198 participants ages 8–21 years old with SpA and sustained inactive disease on standard TNFi dosing to (1) continue standard TNFi dosing, (2) fixed longer dosing intervals of TNFi, or (3) stop TNFi. The trial will compare the hazard rate of protocol-defined flare and participants’ emotional health among the 3 groups over 12 months. Innovative aspects of this trial are the involvement of patient and parent stakeholders in the design and conduct of the study as well as an electronic health record-based enhanced recruitment strategy. Discussion This is the first randomized pragmatic trial to assess the efficacy of TNFi de-escalation strategies in children with JSpA with sustained inactive disease. This research will improve the evidence base that patients, caregivers, and rheumatologists use to make shared decisions about continued treatment versus de-escalation of TNFi therapy in this population. Trial registration ClinicalTrials.gov NCT04891640. Registered on 18 May 2021.